Disrupting Reconsolidation by Systemic Inhibition of mTOR Kinase via Rapamycin Reduces Cocaine-Seeking Behavior - Zhang, Fushen; Huang, Shihao; Bu, Haiyan; Zhou, Yu; Chen, Lixiang; Kang, Ziliu; Chen, Liangpei; Yan, He; Yang, Chang; Yan, Jie; Jian, Xiaohong; Luo, Yixiao (Frontiers in Pharmacology, 2021)
Drug addiction is considered as an abnormal type of learning, and drug-related memories aroused by the presence of drug related stimuli (drug context or drug-associated cues) promote recurring craving and reinstatement. The mammalian target of rapamycin (mTOR) signaling pathway is involved in reconsolidation of drug memories in conditioned place preference (CPP) and alcohol self-administration (SA) models. Here, we explored the effect of mTOR inhibition on reconsolidation of addiction memory using cocaine SA model. Rats received self-administration of intravenous cocaine training for consecutive 10 days, during which a light/tone conditioned stimulus (CS) was paired with each injection. After acquisition of the stable cocaine self-administration behaviors, rats were subjected to nosepoke extinction (11 days) to extinguish the behaviors, and then received a 15 minutes retrieval trial with cocaine-paired tone/light cue delivery or without. Immediately or 6 hours after the retrieval trial, rapamycin (10mg/kg) was administered intraperitoneally. Finally, cue-induced reinstatement, cocaine-priming-induced reinstatement and spontaneous recovery of cocaine-seeking behaviors were tested, respectively. We found that rapamycin injection immediately after retrieval trial decreased subsequent reinstatement induced by cues or cocaine priming, and these effects lasted at least for 28 days. In contrast, delayed intraperitoneal injection of rapamycin 6 hours after retrieval or rapamycin injection without retrieval had no effects on cocaine-seeking behaviors. These findings indicated that mTOR inhibition within the reconsolidation time-window impairs the reconsolidation of cocaine associated memory, reduces cocaine-seeking behavior and prevents relapse, which is retrieval-dependent and temporal-specific.